2012
DOI: 10.4049/jimmunol.1102828
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1–Mediated Negative Signaling Plays a Critical Role in the Induction of Regulatory Dendritic Cells by DNA and Protein Coimmunization

Abstract: Induction of Ag-specific regulatory T cells (iTregs) by vaccination is a promising strategy for treating autoimmune diseases. We previously demonstrated that DNA and protein covaccination converted naive T cells to Ag-specific iTregs by inducing CD11c+CD40lowIL-10+ regulatory dendritic cells (DCregs). However, it is unclear how coimmunization induces the DCregs. In this paper, we report that the event is initiated by coentry of sequence-matched DNA and protein immunogens into the same DC via caveolae-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…Many studies showed that polysaccharides from TCM increased not only IL-12 but also IL-10 [34,43,44]. IL-10 modulates DC functions to suppress immune responses through induction of Tregs [45,46]. In contrast, our results showed that PFWE did not induce IL-10 production.…”
Section: Discussioncontrasting
confidence: 84%
“…Many studies showed that polysaccharides from TCM increased not only IL-12 but also IL-10 [34,43,44]. IL-10 modulates DC functions to suppress immune responses through induction of Tregs [45,46]. In contrast, our results showed that PFWE did not induce IL-10 production.…”
Section: Discussioncontrasting
confidence: 84%
“…DC2.4 is a DC cell line from C57BL/6 mice. Cav-1 knockdown DC2.4 cells and Cav-1 overexpressing DC2.4 cells were generated as previously described (23). Vero cells and DC2.4 cell lines were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS) and 1% penicillin-streptomycin at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Although best known in lipid metabolism, roles for Cav-1 in the internalization of pathogens, signal transduction, host defenses, and suppression of inflammatory responses have also been indicated by numerous studies (20)(21)(22). Viral entry into cells occurs by clathrin, caveolae, or receptor-mediated pathways (23)(24)(25). However, recent studies revealed that simian virus 40 (SV40) enters cells via an atypical caveolae-mediated endocytic pathway, forming a new compartment called a caveosome (26,27).…”
mentioning
confidence: 99%
“…Immature or induced regulatory DCs (DC reg ) can promote tolerance by converting naïve T cells into the CD4+Foxp3+ regulatory T cells (157). DC differentiation into DC reg requires DNA and protein cotreatment and this is inhibited by the activation of Cav-1 and increased Tollip protein to initiate negative signaling, which leads to downregulation of STAT-1α and NF-κB, and expression of the DC reg phenotype (97). In this study, Cav-1/caveolae mediated couptake of DNA and protein immunogens via endocytosis and Cav-1 activation by phosphorylation to form a negative signaling complex to suppress IRAK-1's kinase activity (119) suggesting that Cav-1 plays a critical role in modulation of the DC phenotype and function.…”
Section: Dendritic Cellsmentioning
confidence: 99%